Assessment of local risk factors of periodontal disease in children and adolescents - Golubeva, Інна Миколаївна; Ostapko, Олена Іванівна (Actual Dentistry, 2024)
The aim of the study. To investigate the periodontal status in children and adolescents with gingivitis and localized periodontitis and to assess the influence of local risk factors on the development of periodontal diseases. Materials and methods. 160 children and adolescents aged 12 to 17 years were examined at the Dental Medical Center of the Bogomolets National Medical University. All participants were examined for periodontal status, oral hygiene, and local risk factors of periodontal diseases. Research results. A high prevalence of gingivitis associated with dental biofilm in children and adolescents aged 12-17 was determined — 88.7%. Localized periodontitis of initial stage was diagnosed in 7.5% of participants. A statistically significant worsening of the periodontal status in adolescence was registered. The most significant risk factors of the periodontal diseases development were unsatisfactory individual oral hygiene and maxillofacial anomalies, which accounted for about 75% patients. In the presence of an inflammatory process in the gums, crowding of teeth, distal and deep bite prevailed. In the case of localized periodontitis, the crowded position of the frontal teeth in lower jaw was most often observed. Carious cavities and restorations of proximal localization (38.0%) were the second most common cause of gingivitis. Anomalies of soft tissues attachment played a significant role in the development of periodontitis. These include shortening of the lower lip frenullum (41.7%) and a small vestibullum of oral cavity in the area of the lower frontal teeth (33.3%). Conclusions. The high prevalence of periodontal diseases in children and adolescents is due to unsatisfactory personal oral hygiene against the background of the negative impact of local risk factors — maxillofacial anomalies, carious cavities and proximal restorations, anomalies of soft tissues attachment in the oral cavity. Therefore, the priority direction of modernperiodontology should be an interdisciplinary approach in primary prevention, which will contribute to the improvement of periodontal health and the quality of life in children and adults of Ukraine. Keywords: children, adolescents, gingivitis, periodontitis, periodontal status, local risk factors.